Medial patellofemoral ligament reconstruction normalizes patellar kinematics but fails to predict cartilage contact area: A prospective 3D MRI study - Markus Siegel; Philipp Maier; Elham Taghizadeh; Hans Meine; Thomas Lange; Andreas Fuchs; Tayfun Yilmaz; Hagen Schmal; Kaywan Izadpanah (Journal of Experimental Orthopaedics)
Abstract Introduction The medial patellofemoral ligament (MPFL) is the main patellar stabilizer in low knee flexion degrees (0–30°). Isolated MPFL reconstruction (MPFLr) is therefore considered the gold standard of surgical procedures for low flexion patellofemoral instabilities (PFIs). Despite excellent clinical results, little is known about the effect of MPFLr on kinematic parameters (KPs) of the patellofemoral joint in vivo. This study investigates the effect of MPFLr on KP of patellofemoral articulation, using a three‐dimensional (3D) in vivo magnetic resonance imaging (MRI) analysis at different flexion and loading positions, and analyzes the correlation of these parameters with the patellofemoral cartilage contact area (CCA). Methods In this prospective, matched‐pair cohort study of 30 individuals, 15 patients with low flexion PFI and 15 knee‐healthy individuals were included. Patients were analyzed pre and post‐operatively after MPFLr. MRI images were obtained at 0°, 15° and 30° with and without muscle activation, using a custom‐designed pneumatic loading device. Patellar shift, tilt and rotation were determined in 3D bone and cartilage models of each individual, guaranteeing the highest reliability. Subsequently, the KPs were correlated with patellofemoral CCA. Results Patients with low flexion PFI had a leg geometry of 0.5 ± 2.6° valgus and a TTTG of 11.4 ± 4.4 mm. Eleven patients had moderate (Type A/B) and 2 had severe (Type C/D) trochlear dysplasia. Without muscle activation, patients showed significantly increased patellar shift (0–30°; p0° = 0.011, p15° = 0.004 and p30° = 0.015) and tilt (15°; p15° = 0.041). Muscle activation did not compensate for maltracking in these patients, but even increased tilt and shift further in extension (p0° = 0.002 and p0° = 0.001). MPFLr statistically reduced patellofemoral tilt from 0° to 30° flexion during passive flexion and tended to approach the values of knee‐healthy individuals (pext = 0.008, p15° = 0.006 and p30° = 0.003). Post‐operatively, muscle activation led to comparable tilt and shift as in healthy individuals. Tilt, shift and rotation did not correlate with CCA neither in healthy individuals nor in pre‐ or post‐operative patients. Conclusion Isolated MPFLr can normalize patellar shift and tilt in patients with low flexion instability. Considering the influence of muscle activation, passive stabilization through MPFLr seems to be the basic precondition for physiologically active patella stabilization. The investigated KPs as easy‐to‐measure parameters in clinical practice cannot be used to assume normalized CCA for low flexion degrees. Therefore, methodologically demanding methods are still required to calculate the patellofemoral CCA. Level of Evidence Level II.